The Generalized Pathology of Our Era: Comparing the Biomedical Explanation, the Cultural-Political Explanation, and a Liberal-Humanistic-Postmodernist Perspective. Issue 1 (2nd January 2017) - Ratner, Carl
ABSTRACT: This article seeks to problematize the issue of pathology and to render it intelligible. I elucidate a cultural-political model of a) why pathology is prevalent in numerous forms and social domains, and b) interventions for ameliorating widespread pathology, and ultimately eradicating it. This model draws on the work of Eric Fromm that articulates how pathology is characteristic of normal social, psychological activity in many or most societies. This article also discusses two ways in which prevalent pathology is misunderstood, and not corrected, eradicated, or prevented. One misinterpretation is the standard biomedical model of pathology. A second misinterpretation is a liberal, humanistic, postmodern position that denies all pathology and insists that behavior is a positive expression of choice and agency, which must be validated and accepted rather than corrected.